The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1103/physrevlett.90.203401
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Interatomic Coulombic Decay in Ne Clusters

Abstract: Electron spectra of photoexcited Ne clusters are shown to display a signal at low kinetic energies that is neither present in the Ne monomer nor at photon energies below the inner-valence 2s threshold. These findings are strong evidence for the existence of interatomic Coulombic decays (ICD), a mechanism that was recently predicted theoretically [Phys. Rev. Lett. 79, 4778 (1997)]. In ICD, an inner-valence hole state in a weakly bonded system can undergo ultrafast relaxation due to energy transfer to a neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
278
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(293 citation statements)
references
References 21 publications
(24 reference statements)
9
278
1
Order By: Relevance
“…[10][11] In recent years a set of novel non-local autoionization processes has been identified to play an important role in weakly bonded atomic and molecular systems. [12][13][14] One such relaxation process is Intermolecular Coulombic Decay (ICD), initially observed upon innervalence ionization of van der Waals-bonded clusters, 12,[15][16][17] and later also (hydrogen bonded) water clusters. 18 In the ICD process, the energy provided by an outer valence electron upon filling the vacancy is used to expel a second electron from an atom or molecule neighboring the initially ionized site.…”
Section: Identifying the Initial Products Of The Interaction Of High-mentioning
confidence: 99%
“…[10][11] In recent years a set of novel non-local autoionization processes has been identified to play an important role in weakly bonded atomic and molecular systems. [12][13][14] One such relaxation process is Intermolecular Coulombic Decay (ICD), initially observed upon innervalence ionization of van der Waals-bonded clusters, 12,[15][16][17] and later also (hydrogen bonded) water clusters. 18 In the ICD process, the energy provided by an outer valence electron upon filling the vacancy is used to expel a second electron from an atom or molecule neighboring the initially ionized site.…”
Section: Identifying the Initial Products Of The Interaction Of High-mentioning
confidence: 99%
“…As ICD occurs, the energy of an excited atom in van der Waals or hydrogen bound matter is used to release a low energy electron from a neighboring atom. During the last three years, the existence of ICD has been proven experimentally by means of electron spectroscopy [2] and multiparticle coincidence momentum spectroscopy techniques (COLTRIMS) [3]. Later experimental evidence of ICD in species other than a neon cluster was found, as well [4].…”
mentioning
confidence: 99%
“…For the case of ICD after 2s photoionization in neon dimers, the decay rate is proportional to jV L2p;R2p;L2s;k ÿ V L2p;R2p;k;L2s j 2 , where the two electron-electron Coulomb matrix elements (2) are denoted as ''direct'' and ''exchange'' contribution, respectively [6,12]. These two matrix elements are schematically illustrated in Fig.…”
mentioning
confidence: 99%
“…Upon core level photoionization, the created hole state undergoes ultrafast relaxation due to energy transfer to a neighbouring atom, and emits an electron from that neighbouring site. [11][12][13] The first successful attempt to measure non-protonated (H 2 O) n + (2≤n≤10) clusters was by Shinohara et al 14 who used the argon emission lines at 11.62 and 11.83 eV to ionize a mixed argon/water molecular beam. Since protonated water clusters and mixed (H 2 O) n Ar m + clusters were also observed, it was suggested that electron emission and Ar evaporation from these clusters led to the formation of the non-protonated species.…”
mentioning
confidence: 99%